Progress Towards Elimination of Trachoma as a Public Health Problem in Eritrea: Results of a Systematic Review and Nine Population-based Prevalence Surveys Conducted in 2014. (28th December 2018) - Tesfazion, Andeberhan; Zecarias, Alem; Zewengiel, Solomon; Willis, Rebecca; Mebrahtu, Goitom; Capa, Eva; Mpyet, Caleb; Al-Khatib, Tawfik; Courtright, Paul; Solomon, Anthony W.
ABSTRACT: Purpose : To assess Eritrea's progress towards elimination of trachoma as a public health problem, we reviewed and compiled current knowledge on the distribution and burden of trachoma in Eritrea, then undertook further population-based surveys where indicated, with support from the Global Trachoma Mapping Project (GTMP). Methods : For the systematic review, undertaken in March 2014, we searched (1) PubMed, using the terms ((blind* or trachoma or trichiasis) AND Eritrea); (2) the online database of rapid assessments of avoidable blindness; (3) our own grey literature collections; and (4) the Global Atlas of Trachoma database. In June and July 2014, we conducted nine population-based prevalence surveys, for each of which 30 villages were systematically selected with probability proportional to population size; in each village, 30 households were systematically selected. All consenting residents of selected households aged ≥1 year were examined by GTMP-certified graders for signs of trachoma. Data on household-level access to water and sanitation were also collected. Results : One previous rapid assessment of avoidable blindness, three peer-reviewed publications, and two grey literature reports detailing sets of trachoma prevalence surveys conducted in 2006 and 2011, respectively, were located. Post-intervention impact surveys were needed in seven evaluation units (EUs, framed at sub-Zoba-level: population range 40, 000–120, 000) of Debub and Northern Red Sea, while baseline surveys were needed in two EUs of Anseba. Four of the seven impact survey EUs and both baseline survey EUs returned trachomatous inflammation—follicular prevalences in 1–9-year-olds of ≥5%; six of the seven impact survey EUs and one of the two baseline survey EUs returned trichiasis prevalences in ≥15-year-olds of ≥0.2%. The prevalence of access to water and sanitation varied widely between EUs. Conclusion : Interventions are still required in Eritrea to eliminate trachoma as a public health problem. Data from these surveys will guide the Ministry of Health to undertake programme planning using a sound evidence base.